2018
DOI: 10.18240/ijo.2018.01.15
|View full text |Cite
|
Sign up to set email alerts
|

Final anatomic and visual outcomes appear independent of duration of silicone oil intraocular tamponade in complex retinal detachment surgery

Abstract: Anatomic and visual outcomes in this cohort are in keeping with those reported in the literature. Favorable outcomes were seen with oil removal but duration of oil tamponade does not affect final attachment rate with modern surgical techniques and should be managed on a case by case basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…According to our data, the duration of SO endotamponade did not impact the visual outcome. Previous studies have reported similar results [ 4 , 22 ]. However, our cohort had a relatively homogeneous time frame, in which the SO remained in the patients’ vitreous cavities, ranging from six to fifteen weeks, which limits the significance of these results.…”
Section: Discussionsupporting
confidence: 84%
“…According to our data, the duration of SO endotamponade did not impact the visual outcome. Previous studies have reported similar results [ 4 , 22 ]. However, our cohort had a relatively homogeneous time frame, in which the SO remained in the patients’ vitreous cavities, ranging from six to fifteen weeks, which limits the significance of these results.…”
Section: Discussionsupporting
confidence: 84%
“…One of the major reasons for the absence of definitive agreement is the lack of knowledge about in vivo emulsification process of SO intraocularly and its variations among patients (Ni et al 2019). In fact, some clinicians have shown that prolonged SO tamponade does not increase those risks significantly (Pavlovic et al 1995;Lam et al 2008;Rhatigan et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Silicone oil (SO) is a safe and well-tolerated intraocular tamponade agent widely used for the treatment of complicated vitreoretinal diseases such as inferior rhegmatogenous retinal detachments (RRDs), proliferative vitreoretinopathy (PVR), giant retinal tears, traumatic retinal detachments, and some cases of tractional retinal detachments 1 . As SO is less dense than water, SO has positive buoyancy and floats, and the contact angle is smaller than that of gas to the retina 2 .…”
Section: Introductionmentioning
confidence: 99%